Mouse Trophoblast Cells Are Constitutive Producers of Thromboplastin (Factor III) In Vitro - Dalaker, K; Haug, E; Prydz, H (Thrombosis and Haemostasis, 1985)
Trophoblasts from murine placenta synthesize thromboplastin in the absence of inducing agents and a functional complement system, nor is the rate or level of synthesis enhanced by inducers. A serum factor which is destroyed/removed by addition of oxalate and subsequent dialysis appears to enhance the ability of trophoblasts to synthesize thromboplastin.
Keywords: Thromboplastin; Tissue factor; Trophoblasts; Placenta; Synthesis; Cell culture